2019
DOI: 10.1108/nfs-01-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

The role of melatonin supplement in metabolic syndrome

Abstract: Purpose Metabolic syndrome contains metabolic disorders that have association with other chronic diseases. Melatonin is a bioactive compound which is found in plants and also produced in the body. The purpose of this paper is to assess the effect of melatonin supplement on metabolic syndrome components, also leptin and adiponectin blood concentrations in patients with metabolic syndrome. Design/methodology/approach A double blind, placebo-controlled, randomized clinical trial was conducted on 70 subjects wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…It is worth mentioning that both groups underwent supplementation (melatonin or placebo) and a calorie-restricted diet. A similar result was observed by Bahrami et al 66 in a study of 12 weeks of supplementation with 6 mg of melatonin (one hour before the desired time to sleep) in 70 individuals with metabolic syndrome. The authors found a significant reduction in body weight, waist, and abdominal circumference, in addition to a tendency to reduce BMI in comparison with the placebo.…”
Section: Marqueze Et Alsupporting
confidence: 85%
“…It is worth mentioning that both groups underwent supplementation (melatonin or placebo) and a calorie-restricted diet. A similar result was observed by Bahrami et al 66 in a study of 12 weeks of supplementation with 6 mg of melatonin (one hour before the desired time to sleep) in 70 individuals with metabolic syndrome. The authors found a significant reduction in body weight, waist, and abdominal circumference, in addition to a tendency to reduce BMI in comparison with the placebo.…”
Section: Marqueze Et Alsupporting
confidence: 85%
“…The findings were also lower as compared to Palestine (37.0%) [ 70 ], the Greek population (43.4%) [ 71 ], and the population of Nepal (52.7%) [ 72 ]. The variation in reports might be due to the difference in the underling important risk factors such as urbanization, westernization of lifestyle including unhealthy diet and physical inactivity [ 73 ], mental stress due to economic, social, and cultural factors [ 74 ], genetics, proinflammatory condition [ 75 ], intrauterine growth retardation, and over nutrition increasing on top of the already high prevalence of under nutrition [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…After duplicate removal, abstract screening and full-text reviews, eleven studies were included in the systematic review and meta-analysis and none was found to have been published in a predatory journal. [15][16][17][18][27][28][29][30][31][32][33]…”
Section: Study Selectionmentioning
confidence: 99%
“…The summarized study characteristics are prestend in Table 1 and a structured risk of bias assessment in the individual studies are presented in Table 2. Seven studies had low risk of bias 16,17,28,[30][31][32][33] and four studies had some concerns. 15,18,27,29 Abood et al 27 randomized 40 women with metabolic syndrome 1:1 to receive either 500 mg metformin × 2 and placebo × 1 or 500 mg metformin × 2 and 10 mg melatonin × 1 for 90 days.…”
Section: Study Characteristics and Risk Of Bias Within Studiesmentioning
confidence: 99%